Pathways to cures for multiple sclerosis: A research roadmap. (March 2022) - Bebo, Bruce F; Allegretta, Mark; Landsman, Douglas; Zackowski, Kathy M; Brabazon, Fiona; Kostich, Walter A; Coetzee, Timothy; Ng, Alexander Victor; Marrie, Ruth Ann; Monk, Kelly R; Bar-Or, Amit; Whitacre, Caroline C
Background: Multiple Sclerosis (MS) is a growing global health challenge affecting nearly 3 million people. Progress has been made in the understanding and treatment of MS over the last several decades, but cures remain elusive. The National MS Society is focused on achieving cures for MS. Objectives: Cures for MS will be hastened by having a roadmap that describes knowledge gaps, milestones, and research priorities. In this report, we share the Pathways to Cures Research Roadmap and recommendations for strategies to accelerate the development of MS cures. Methods: The Roadmap was developed through engagement of scientific thought leaders and people affected by MS from North America and the United Kingdom. It also included the perspectives of over 300 people living with MS and was endorsed by many leading MS organizations. Results: The Roadmap consist of three distinct but overlapping cure pathways: (1) stopping the MS disease process, (2) restoring lost function by reversing damage and symptoms, and (3) ending MS through prevention. Better alignment and focus of global resources on high priority research questions are also recommended. Conclusions: We hope the Roadmap will inspire greater collaboration and alignment of global resources that accelerate scientific breakthroughs leading to cures for MS.